Pyrocarbon proximal interphalangeal joint arthroplasty: a medium to long term follow-up of a single surgeon series. (November 2015) - Storey, P. A.; Goddard, M.; Clegg, C.; Birks, M. E.; Bostock, S. H.
We retrospectively reviewed a consecutive single surgeon series of 57 Ascension pyrocarbon proximal interphalangeal joint arthroplasties, with a mean follow-up of 7.1 years (range 2 years to 11 years 6 months). We assessed the ranges of motion, deformity, stability and pain of the operated joints, grip strength of the hand and patient satisfaction. Of the cases, 44 were for osteoarthritis, five for rheumatoid arthritis and eight for post-traumatic arthritis. The median post-operative active arc of motion was from 0° to 60°. The median post-operative visual analogue pain score was 0.3 out of ten. Thirty six of the joints had no complications; 14 had minor complications (squeak, slight swan neck); three required early reoperation (joint release, flexor tenodesis); and five required implant removal. A total of 69% of our patients would have the same operation if they had to make the decision again. The Kaplan-Meier survival method estimates the mean implant survival to be 10.7 years (95% confidence intervals 9.96–11.37 years). All five failures occurred during the first 2 years. Level of evidence 4 (Case-series).